Minho MSL: a new generation of soccer robots - Ribeiro, A. Fernando (2011)
This paper describes the new generation of Minho Team robots since the last RoboCup participation. Robots have been rebuilt from top to bottom, keeping the essence of the previous generation, but lighter, faster, improved sight, new algorithms and new technology. The demands of RoboCup MSL are very high and a new breed of robots was necessary to cope with it. This paper describes a bottom-up view of the robot, the hardware used, the vision head, the high level software and some conclusions.